J.K.Lasser's your income tax 2008 : (J. Wiley, 2007)
J.K. Lasser’s Your Income Tax, Professional Edition 2008 is an essential guide for tax professionals. Filled with easy-to-use tax planning tips and strategies, this comprehensive guide arms you with the information you need to maximize your clients’ tax savings. Completely updated with all the latest tax law changes, this guide makes preparing 2007 tax returns easier than ever.